Guía “De regreso al trabajo”, necesidad empresarial para la adecuada implementación de los procesos de rehabilitación, reincorporación y reubicación laboral dentro del sistema de gestión de seguridad y salud en el trabajo (2019)
The socio-occupational integration is considered as the professional rehabilitation’s immediate objective and the integral rehabilitation’s goal. Its intervention is oriented to the recovery and development of the capability of the person who has suffered some capacity decrease to exercise a function or a position, to perform productive functions in different contexts, based on the quality standards established by the productive sector; the rehabilitation, reincorporation or labor relocation processes are poorly known by employers and information about them is scarce and little standardized, which difficults their final success. Therefore, through this qualitative research, developed through a review of the matter’s state of the art, we look up to build a technical document - instructional and pedagogical, called "back to work", which will allow those in charge of the System Occupational Health and Safety Management, Human Resource Managers, Executives and others involved in the process, effectively apply these strategies to reduce time losses due to temporary disability and for the worker to succesfully return to the work environment, maintaining its role as a society’s productive actor.